2021
DOI: 10.1016/j.solener.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial modification of perovskite solar cells via Cs2CO3: Computational and experimental approach

Abstract: Interfacial materials in perovskite solar cells (PSCs) between the absorber layer and charge selective layers are stimulants to boost performance and long-term stability. Incorporation of a low-temperature processed passivating agent at electron selective layer/perovskite interface can enhance the performance of PSCs, however, the interface at SnO2/(FAPbI3)0.85(MAPbBr3)0.15 suffers from surface phenomena that retard the overall performance of the PSCs. By adopting a synergistic approach, drift-diffusion simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Numerous recent studies have revealed that the structure–activity relationship in perovskite surface passivating agents is not straightforward, 20 a ,22 and that the modification of the electronic properties or operational lifetime may result from effects that are specific to individual systems. 23 For example, when comparing the effect of 4-fluorophenethylammonium iodide (F-PEAI) 24 with its non-fluorinated analogue (PEAI), 8 a it was observed that F-PEAI-treated devices show enhanced stability when exposed to humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous recent studies have revealed that the structure–activity relationship in perovskite surface passivating agents is not straightforward, 20 a ,22 and that the modification of the electronic properties or operational lifetime may result from effects that are specific to individual systems. 23 For example, when comparing the effect of 4-fluorophenethylammonium iodide (F-PEAI) 24 with its non-fluorinated analogue (PEAI), 8 a it was observed that F-PEAI-treated devices show enhanced stability when exposed to humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Good performances in terms of reducing dark current density can be achieved in sandwich structure OPDs with the presence of an electrode buffer layer. Electrode buffer layers composed of various wide bandgap n-type metal oxides, such as ZnO, [25,26] TiO 2 , [27,28] and Cs 2 CO 3 , [29,30] have often been utilized in optoelectronic devices. Cs 2 CO 3 , in particular, has gained popularity due to its low cost, high electron mobility, and high transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…Cesium carbonate (Cs 2 CO 3 ) is an excellent interface modification material widely used in organic light emitting diodes (OLED), organic solar cells (OSCs), organic field-effect transistors (OFET) and other devices. Cs 2 CO 3 can also be used as an interfacial passivation layer for ETL/perovskite to improve the efficiency of perovskite solar cells by reducing the recombination rate at the interface [9]. We have used Cs 2 CO 3 to electrically modify the electron transport layer (ETL) of p-i-n type PeSCs and improved device efficiency [10].…”
mentioning
confidence: 99%